PHENOMENOGRAPHY ANALYSIS OF STUDENTS’ HISTORICAL THINKING ABILITY IN STUDYING SOCIAL HISTORY - Agus Mulyana; Yeni Kurniawati (Jurnal Cakrawala Pendidikan, 2020)
The Marton Phenomenography Analysis model is interesting to apply because it has a significant characteristic of learning that is based on two academic learning patterns, namely "surface" and "in-depth" learning approaches. This study aimed to investigate students’ historical thinking ability using the Marton Phenomenography Analysis. Qualitative method was utilized with a phenomenography approach. The phenomenography approach was aimed to identify students’ historical thinking ability as they experience, conceptualize, perceive, and understand various historical phenomena of social movements. The subjects were students who took part in Social History. Data were collected from examination, observation, interviews and document study. The results showed that students who have "surface" and "in-depth" learning patterns have different thinking patterns, perspectives, and perceptions. There is a significant difference as much as 12.11% in the historical thinking ability between both groups. The "in-depth" group has an advantage over the "surface" group in terms of understanding changes, comparing historical narratives, interpreting history, understanding historical interpretation, as well as constructing history. Both the "in-depth" and "surface" groups have a good ability in the aspect of knowledge on facts and how to search for historical sources. Finally, both groups have less ability to develop different thinking patterns, create questions from historical stories, and evaluate historical sources.